Technology differentiation, product market rivalry, and M&A transactions - Arts, Sam; Cassiman, Bruno; Hou, Jianan (Strategic Management Journal, 2025)
Research Summary We study how unique firm technology influences M&A activity. Using a text‐based network approach, we map each firm's position relative to every other firm in technology space to measure the uniqueness of its technology portfolio. Our findings indicate that firms with more unique technology portfolios become prime acquisition targets, particularly for close competitors within the same product market segments. These competitors seek to reduce competition and incorporate unique technologies to strengthen their competitive advantage. Furthermore, firms with unique technology portfolios tend to attract acquirers with closer technological proximity, facilitating the evaluation and integration of these technology assets. Our study underscores unique technology as a critical asset in the market for corporate control and a key driver of M&A transactions. Managerial Summary In today's high‐tech business environment, M&As are pivotal strategies not just for growth and competitiveness but often specifically aimed at acquiring the technology of target firms. By analyzing US public firms, we demonstrate that those with unique technology portfolios attract more acquisition interest, particularly from close product market rivals. These rivals aim to reduce competition and strengthen their existing product business by incorporating the unique technology. Companies with unique technology are also particularly appealing to those within closer technological proximity, easing the evaluation and integration process. Our findings emphasize that possessing a unique technology portfolio is a vital asset in the market for corporate control and a major catalyst for mergers and acquisitions activities.